Probing the dual function of a novel tertiary amine compound in dentin adhesive formulations. Issue 4 (April 2016) - Ge, Xueping; Ye, Qiang; Song, Linyong; Laurence, Jennifer S.; Misra, Anil; Spencer, Paulette
Abstract: Objectives: A novel tertiary amine compound containing three methacrylate-urethane groups was synthesized for application in dentin adhesives. The synthesis, photopolymerization kinetics, and leaching were examined in an earlier study using this novel compound as the co-initiator (0.5 and 1.75 wt% based on the total resin mass). The objective of this work was to investigate the potential of TUMA (8-(2-(((2-(methacryloyloxy)ethyl)carbamoyl)oxy)propyl)-6, 10-dimethyl-4, 12-dioxo-5, 11-dioxa-3, 8, 13-triazapentadecane-1, 15-diyl bis(2-methylacrylate)) to serve simultaneously as a co-initiator and co-monomer (15–45 wt% based on the total resin mass) in dentin adhesive formulations. The polymerization kinetics, water sorption and dynamic mechanical properties of these novel formulations were determined. Materials and method: The monomer system contained Bisphenol A glycerolate dimethacrylate (BisGMA), 2-hydroxyethylmethacrylate (HEMA) and TUMA (synthesized in our lab) at the mass ratio of 45/(55-x)/x. Two photoinitiator (PI) systems were compared. One initiator system contains three components: camphorquinone (CQ), diphenyliodonium hexafluorophosphate (DPIHP) and ethyl-4-(dimethylamino) benzoate (EDMAB) and the second initiator system contains CQ and DPIHP. The control adhesive formulations are: C0-3: HEMA/BisGMA 45/55 (w/w) and 3-component PI and C0-2: HEMA/BisGMA 45/55 (w/w) and 2-component PI. These controls were used as a comparison to the experimental adhesive resins (Ex-3 or Ex-2), in which x represents the weight percentage of synthesized co-monomer (TUMA) to replace part of BisGMA. The control and experimental adhesive formulations were photo-polymerized and compared with regard to the degree of conversion (DC), polymerization rate (Rp), water sorption and dynamic mechanical analysis (DMA) under both dry and wet conditions. Results: C0-3 and Ex-3 formulations had similar DC, while the DC of Ex-2 formulation was higher than C0-2. The DC was similar when comparing the two- component with the three-component photoinitiator system when TUMA was used at the same concentration. DMA under dry conditions shows higher rubbery storage modulus for all experimental formulations, while storage modulus at rubbery region under wet conditions was decreased as compared with control (C0-3). There was no statistically significant difference for the DMA results under both dry and wet conditions when comparing two- and three-component initiator systems with the same TUMA concentration. Significance: The newly synthesized TUMA could serve simultaneously as a co-monomer and co-initiator in the absence of commercial co-initiator. This study provides information for the future development of new co-monomer/co-initiator for dentin adhesives and dental composites.